A critique of the appropriateness of the investment lifecycle model in Zimbabwe - Muchemedzi, Kunaka B.S, (Midlands State University, 2017)
The study seeks to investigate the compatibility of the generalisations of the investment life cycle model in Zimbabwe. In that it contrasts the economic condition of Zimbabwe with chosen benchmarks of efficient economies which are USA and RAS. A comparative study of descriptive statistics is employed in carrying out this study with ratio analysis on selected macro-economic variables including inflation and economic output measures. Data will be collected from documents published by central banks, neutral bodies such as UN and IMF so as to complement country central records of the involved economies. The descriptive statistics showed economic decline from 2000 to 2009, this is indicated by the inflationary rate of 241 million in 2009, a decline by 27.1% of the gross domestic output, the decline of the gross fixed capital formation from 10.6% to 4.3% and decline in other variables such as trade openness and financial market trends. This gave a conclusion that the Zimbabwe had an irregular economic condition in the period mentioned that did not sustain investment and increased pressure on personal income through increased consumption expenditure. Capital preservation and appreciation was disabled due to uncertainty and absence of intelligible financial instruments on financial markets.The economic condition the investment life cycle model assumes is to be achieved before it can be applicable to a country. This model can be used as an integral proxy to measurement of the standard of living for the general population in Zimbabwe and its generalisations can used as objectives in economic reform strategies.